Economics of Non-Timber Forest Production Promotion and Marketing: A case study from Malekhukhola Watershed of Dhading District, Nepal - Pandit, Bishnu Hari (The Initiation, 2010)
This article examines the prospects of promoting NTFPs in the mountains of Nepal. Despite being profitable, the farmers do not readily accept cultivating NTFP species on their farmlands on a large scale. The analyses revealed that domestication of MAP species is significantly influenced by various factors such as, knowledge and skill required for domestication, frequency of visits to forest, the length of fallow period, size of upland terraces, cattle and goat herd size, accessibility to forest, inappropriate permit system, difficult trading system and market uncertainty. The inappropriate NTFP permit system, difficult trading system and free access to forest have negatively influenced domestication of MAP species. Overall, lack of a favorable institutional environment has been the major factor constraining the integration of NTFP species into farmland on a large scale by farmers. Policy recommendations include handing over the use and management responsibility to local people, to that prevent open access status of national forests, providing NTFP collection permits to local residents, lobbying for amending inappropriate policies, rules and regulations, promoting group marketing and adaptive collaborative forest management approach to community forestry. Key Words: NTFP collection, Marketing, Domestication, Factors affecting MAP domestication DOI: 10.3126/init.v2i1.2537 The Initiation Vol.2(1) 2008 pp145-156